The development of Muslim-friendly event management standards in Malaysia for establishment of Malaysian Shariah index compliance - Zainan Nazri, Nurul Jannah; Fatah Yasin, Raudlotul Firdaus; Samsudin, Sofiah; Ahmad, Sakiroh (Springer, 2018)
The International Organization for Standardization has realized the importance of providing standards and guidelines for event management, which ultimately led to the existence of event management standard; ‘ISO 20121: 2012 Event sustainability management systems - Requirements with guidance for using it in 2012”. Indeed, it was started earlier by the British Standard for ‘BS8901 Event Management Standard’ in 2005. However, the previous mentioned standards are not fully complied with the Shariah. The present study focuses on developing a sustainable ‘Muslim friendly’ standards of event management in Malaysia as a Muslim-majority country. By applying textual analysis method on the Qur’anic verses and the Prophetic hadith related to event management, the study finds several important Guiding Principles (GP) and values for Shariah compliance event management standards (SCEMS); Al-Tawhid (Divine Unity), alWasatiyyah (the Moderation), al-Tawazun (the Balance), al-‘Adl (the Justice), al-Ihsan (the Excellence), al-Itqan (the Quality) and Maqasid al-Shariah (The Goals of Shariah). All of these elements are built on a comprehensive understanding of the concept of Islam as a Din and a way of life which promotes moderation and balance in all matters as well as considers the diversity of faith, including the non-Muslim sentiments. The content and the process of organizing an event, which involves three basic phases; altakhtit (planning), al-tanzim (organizing) and al-riqabah (controlling) of the event are the most important Shariah critical point that must adhere to the GP. The study proposes an eye-bird overview of Shariah compliance event management standards which are vital in achieving the aim of Malaysia to be the Shariah Compliance Hub in the world.